Preliminary analysis of self-reported quality health indicators of patients on opioid agonist therapy at specialty and primary care clinics in Ukraine: A randomized control trial - Oleksandra Pashchenko; Daniel J. Bromberg; Kostyantyn Dumchev; Katherine LaMonaca; Iryna Pykalo; Myroslava Filippovych; Denise Esserman; Maxim Polonsky; Samy J. Galvez de Leon; Olga Morozova; Sergii Dvoriak; Frederick L. Altice (Public Library of Science (PLoS), 2022)
International agencies recommend integrating addiction treatment into primary care for people who inject drugs (PWID) with opioid use disorder (OUD). Empirical data supporting integration that incorporates comprehensive health outcomes, however, are not known. For this randomized controlled trial in Ukraine, adult PWID with OUD were randomized to receive opioid agonist therapy (OAT) in specialty addiction treatment clinics (SATC) or to primary care clinics (PCCs). For those randomized to PCC, they were subsequently allocated to PCCs where clinicians received pay-for-performance (P4P) incentives (PCC with P4P) or not (PCC without P4P). Participating cities had one of each of the three intervention sites to control for geographic variation. Ongoing tele-education specialty training (OAT, HIV, tuberculosis) was provided to all PCCs. While the primary outcome for the parent trial focuses on patient medical record data, this preliminary analysis focuses on assessment of self-reported achievement of nationally recommended quality health indicators (QHIs) which is summed as a composite QHI score. Secondary outcomes included specialty and primary care QHI subscores. This study occurred from 01/20/2018-11/1/2020 with 818 of 990 randomized participants having complete self-reported data for analysis. Relative to SATC (treatment as usual), the mean composite QHI score was 12.7 (95% CI: 10.1-15.3; p<0.001) percentage points higher at PCCs; similar and significantly higher scores were observed in PCCs compared to SATCs for both primary care (PCC vs SATC: 18.4 [95% CI: 14.8-22.0; p<0.001] and specialty (PCC vs SATC: 5.9 [95% CI: 2.6-9.2; p<0.001] QHI scores. Additionally, the mean composite QHI score was 4.6 (95% CI: 2.0-7.2; p<0.001) points higher in participants with long term (>3 months) experience with OAT compared to participants newly initiating OAT. In summary, PWID with OUD receive greater primary care and specialty healthcare services when receiving OAT at PCCs supported by tele-education relative to treatment as usual provided in SATCs. Clinical trial registration: This trial was registered at clinicaltrials.gov and can be found using the following registration number: NCT04927091.